Analisis Pengaruh Dana Desa, Alokasi Dana Desa dan Pendapatan Asli Desa terhadap Jumlah Penduduk Miskin Desa di Kabupaten Tuban - Tanti Auliya Agustina; Muchtolifah Muchtolifah; Sishadiyati Sishadiyati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to analyse the difference in the Number of rural poor people in Tuban Regency between 2019 and 2020 to examine the effect of the Village Fund, Allocation of village funds (ADD) and Village original income on the Number of rural poor people in Tuban Regency in 2019-2020. The analysis tool used is panel data regression which is testing the hypothesis with the F test, t test and Coefficient of Determination (R2) at an error rate of = 5%. The results of panel data regression analysis with the selected model is the Fixed Effect Model showing that there is a difference in the Number of rural poor people in Tuban Regency between 2019 and 2020, the variables used in the model, namely the Village Fund, Allocation of village funds (ADD) and Village original income are able to explain the variation of the variable Number of rural poor by 85% and 15% are influenced by other factors that are not included in the research variables. Keywords: Village Fund, Allocation of village funds (ADD) and Village original income